Reproductive Characteristics of Local Pig Herds in Landono Subdistrict of South Konawe Regency - Achmad Selamet Aku; Kadek Purnama Anti; La Ode Nafiu; Harapin Hafid (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to find out the reproductive characteristics of local pig herds in South Konawe Regency. The location of the study is determined by pusposive sampling with the consideration that Landono Subdistrict is a pig farming center area. Research is carried out using survey methods or in-person interviews to breeders. The study population was selected by 3 villages based on the largest number of pig herd population with the number of respondents for each village as many as 20 respondents, so that the overall number of respondents amounted to 60 respondents with the determination of respondents of each selected village conducted by Simple Random Sampling. The results showed that the average local pig was adult at 6.16 months of age and mated at 8 months of age. The number of children once born (litter size) 9.16 Tails/births with an average age of cows separated from the mother at the age of 3 months.